Recovering Software Design from Interviews Using the NFR Approach: An Experience Report. (17th April 2014) - Subramanian, Nary; Drager, Steven; McKeever, William
Abstract : In the US Air Force there exist several systems for which design documentation does not exist. Chief reasons for this lack of system documentation include software having been developed several decades ago, natural evolution of software, and software existing mostly in its binary versions. However, the systems are still being used and the US Air Force would like to know the actual designs for the systems so that they may be reengineered for future requirements. Any knowledge of such systems lies mostly with its users and managers. A project was commissioned to recover designs for such systems based on knowledge of systems obtained from stakeholders by interviewing them. In this paper we describe our application of the NFR Approach, where NFR stands for Nonfunctional Requirements, to recover software design of a middleware system used by the Air Force called the Phoenix system. In our project we interviewed stakeholders of the Phoenix system, applied the NFR Approach to recover design artifacts, and validated the artifacts with the design engineers of the Phoenix system. Our study indicated that there was a high correlation between the recovered design and the actual design of the Phoenix system.